ENHANCING STUDENTS' WRITING SKILLS THROUGH THE USE OF PICTURE SERIES - Nurmalawati; Ibnu Hajar; Andriani (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
Writing plays a significant role in teaching and learning the English language, yet it is often regarded as a challenging skill to master. To produce a well-written piece, certain criteria must be met, including content, organization, vocabulary, grammar, and mechanics. Instructional media can be a valuable tool for teachers in facilitating writing instruction. This article explores the use of picture series as an instructional medium to enhance students' writing skills. Picture series are particularly effective because they are engaging and visually represent the chronological sequence of a text. The article reviews relevant theories, regulations, research, and practical applications in teaching writing. It also offers examples of different instructional media, emphasizes the benefits of using picture series to improve writing abilities, and provides a step-by-step guide on implementing picture series in the classroom. The goal of this article is to serve as a resource for teaching writing with picture series and to offer recommendations for future research and practice.